Obesogenic factors in costarican public school environment between 2015-2016 - Calvo Molina, Katherine (2019)
Objective: this descriptive investigation makes an analysis of different school environment factors associated with nutritional status, specifically overweight and obesity, of students enrolled in ten public schools in La Union de Cartago, Costa Rica, during 2015-2016. Methodology: The study determinates the nutritional status and characteristics of the lifestyle of 1268 children. Also snacks taken by students, school meals and food sales within schools were evaluated. In addition, a Geographic Information System (GIS) was used to locate food points of sale and recreation areas within a radius of 400 m around the schools. Results: 35% of the children were overweight. Foods from snacks and those sold inside and outside of schools provide high amounts of energy and low nutritional value. Regarding meals provided in the school’s cafeteria, the portion sizes were not adequate, and an excess of foods containing carbohydrate was served. 47% of the children played electronic games more than three times a week, 65% did not participate in sports activities and there was a lack of physical education classes. Only three schools had recreation areas available and their surroundings in good condition. Conclusion: several factors of the school environment belonging to the microsystem promote overfeeding and sedentary lifestyle, which could be contributing to excess bodyweight in children’s population.